Breakdown and breakthrough : psychotherapy in a new dimension - Field, Nathan, 1924- (Routledge, 1996)
Using vivid examples from his psychotherapeutic practice the author shows how, with the apparent breakdown of the therapeutic method itself, patients can break through to a new level of functioning.